With Drama in Mind : Real learning in imagined worlds. - Baldwin, Patrice (Literacy Collection., 2004)
Discover Your Hidden Talents will show you how to:.: Use drama to support multisensory learning accross a wide range of subjects; Toolkit of multipurpose drama strategies to encourage learning; Masses of photocopiable resource sheets and templates; Includes 5 drama units of work with VAK thinking frames - instantly useable and ideal as templates for future planning. This book is excellent for anyone looking to set up drama in school, breathe new life into their drama teaching, or introduce more creativity into any area of the curriculum. Chair of National Drama, Patrice Baldwin, demonstrates h.